Development and testing of an experimental power system fault demonstrator - Rose, Christopher James; Thomas, David W.P.; Sumner, M.; Christopher, Edward (2015)
In this paper a laboratory demonstrator for the study of power system faults is described. The facility has been developed in order to experimentally investigate a number of fault location and power system protection technologies developed by the authors and their colleagues at higher power levels and with more representative system parameters than has previ¬ously been possible. In addition to describing the facility itself, this paper also describes the validation of a previously studied method using the new demonstrator